The administrative and canonical status of the Belarusian Metropolis during the periods of German occupation and post-war emigration (1941–1956) - Slesarau, Aliaxandr V. (Journal of the Belarusian State University. History, 2020)
The article is devoted to considering the specifics of the administrative and canonical status of the Belarusian Metropolis in the diaspora, during 1946–1956 stayed in the jurisdiction of the Russian Orthodox Church Abroad. The conclusion is drawn about what happened from 1950 to 1956 phasing down the status of the metropolis, which led to the cessation of its existence. One of the most important reasons for the liquidation of the Belarusian Metropolis in the diaspora seems to be the fear of the Russian Orthodox Church Abroad bishop about the possible occurrence of disturbances in church life caused by the national question. The liquidation of the Belarusian Metropolis led to a deeper integration of Belarusian emigrants into the cultural environment of the Russian diaspora.